Disability and Aerial Arts - Erin Ball (Circus: Arts, Life & Sciences)
This writing accompanies the documentary video of a workshop that Erin Ball helped to facilitate in July 2022 for the Disability community (including but not limited to Mad, Deaf, Neurodivergent, and/or Disabled). In this text, Erin Ball, a circus artist who is a double below-knee amputee, discusses embodied personal knowledge as a practitioner and workshop leader in the emerging area of aerial arts that strives for inclusion. Erin describes the philosophical and pedagogical approaches taken to making the aerial workshops more accessible to communities often excluded from circus arts.Ce texte accompagne le documentaire vidéo sur un atelier co-animé par Erin Ball en juillet 2022 à l’intention de la communauté des personnes handicapées (et plus particulièrement des personnes sourdes, neurodivergentes, atteintes de pathologies mentales et/ou handicapées). Dans ce texte, Erin Ball, une artiste de cirque qui est aussi amputée des deux jambes sous le genou, analyse le rôle de la cognition incarnée en tant que praticienne et animatrice d’ateliers dans un domaine émergent – les disciplines aériennes – qui recherche une plus grande inclusivité. Erin décrit les approches philosophiques et pédagogiques qui tendent à rendre les ateliers aériens plus accessibles aux communautés le plus souvent exclues des arts du cirque.The article's corresponding video can be found on YouTube: https://www.youtube.com/watch?v=vIW1uPe76no